(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study is an investigation into the ease and effectiveness of emergency lighting. In the experiment, the evacuation time and elements such as recognition distance, search time, and travel time were compared and analyzed for existing LED emergency lighting and the newly developed image output emergency lighting. This was tested in the process of searching for the emergency lighting at various levels of smoke concentration. In order to examine how information affects evacuation choices of evacuees, image output emergency lighting with smoke detectors were produced and used in the experiments. The results are summarized as follows. First, the recognition distance of the exit in the smoke concentration of 30% was the greatest with the image output emergency lighting. It was determined that the evacuation time was short because the evacuation behavior of the evacuee was detected even from the farthest distance while the evacuee searching for the light of the emergency exit was affected by visual impairment and fear due to the indoor smoke. Second, the recognition distance of the exit in the smoke concentration of 70% was the greatest with the image output emergency lighting. It is judged that this is because evacuees were able to escape the building safely by recognizing the exit in the dense smoke by following along the light of the image output emergency lighting. Third, when the smoke concentration was 100%, the smoke increased, and the existing LED emergency lighting at the top of the exit was not identifiable due to the thick smoke. The image output emergency lighting is displayed on the floor of the passage, so the evacuee was able to accurately recognize the exit by looking at the guidance light of the image output emergency lighting, and evacuate safely.